CYR61—An angiogenic biomarker to early predict the impaired healing in diaphyseal tibial fractures - Sabir Ali; Ajai Singh; Abbas Ali Mahdi; Rajeshwar Nath Srivastava (Journal of Orthopaedic Translation, 2017)
Background: Angiogenesis is a prerequisite for fracture repair, whereas insufficient blood supply is likely to result in impaired healing. In the present study, we aimed to determine the correlation of simple tibial fracture healing outcome with serial estimation of CYR61 expressions in the early phase of healing. Methods: In total, 107 adult fractured patients and 97 healthy controls were analysed. Peripheral blood samples were taken from controls (at once) and fractured patients at 4th, 7th, 10th, 15th, 20th and 28th days of post-fracture follow-ups to quantify the CYR61 mRNA and protein expression by qRT-PCR and Western blotting assay, respectively. Clinic-radiological follow-up was done at 6th, 10th, 16th, 20th, and 24th weeks of post-fracture follow-ups using RUST scores to analyse the fracture healing progression and their final outcomes. Results: By considering controls as Group I (n = 97), as per the clinico-radiological status at 24th week, fracture patients were divided into two groups: Group II (normal healing, n = 91) and Group III (impaired healing, n = 16). Both CYR61 mRNA and protein expressions were lower (baseline) in Group I than in Groups II and III; however, a significant difference was observed only with the Group II. In both groups, expressions of CYR61 mRNA as well as protein gradually upregulated from the baseline to a peak and then declined. Both, the CYR61 mRNA as well as protein expressions were significantly higher at all follow-ups in Group II than in Group III. Mean RUST scores between Group II and Group III showed a significant statistical difference at each follow-up. Significant correlation was found between the CYR61 expressions and the RUST score (fracture healing progression). Conclusion: We conclude that CYR61 expression provides an early prediction of the healing outcomes of simple diaphyseal tibial fractures. The translational potential of this article: Such an approach would benefit not only the patients' wellbeing but also the entire health care system in terms of the cost implications associated with long lasting treatment interventions and hospitalisation. However, the authors recommend further multicentric study with a large sample size to increase the validity, reliability, and generalisability of our observation and inferences.